Responsibilities of Prospective Notaries Undergoing Internships Regarding the Confidentiality of Notarial Deeds - Biduri, Pungki; Fajar Riyanto, Taufan (Jurnal Konstatering, 2026)
Confidentiality of notarial deeds is a fundamental principle of notarial law that serves to guarantee legal certainty, protection of the rights of the parties, and public trust in the notary's position as a public official. Prospective notaries who are undergoing internships have direct access to minutes of deeds and confidential legal data, thus giving rise to legal liability consequences even though they do not yet have the status of a notary. This study aims to analyze the construction of legal liability of prospective notary interns regarding the obligation to maintain the confidentiality of notarial deeds and examine the forms of supervision and legal sanctions for violations of this obligation. The research method uses normative legal research through a statutory and conceptual approach, with data collection techniques in the form of literature studies on laws and regulations, doctrines, and theories of legal liability and legal protection theories. The results of the study indicate that the obligation to maintain the confidentiality of notarial deeds is also inherent in prospective notary interns due to their access and active involvement in notarial activities. The legal liability of prospective notary interns is multidimensional, encompassing criminal, civil, as well as ethical and administrative liability. Supervision of prospective notary interns is carried out through internal mechanisms by supervising notaries and external mechanisms by professional organizations and state institutions, with sanctions that function as preventative and repressive measures to protect the interests of the parties and maintain the dignity of the notary profession. This study emphasizes the urgency of strengthening legal regulations regarding the position and responsibilities of prospective notary interns as an integral part of the national notary legal system.